1980
DOI: 10.1210/jcem-51-5-1123
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Thyroid Function in Euthyroid Subjects with a Family History of Graves' Disease: A Foliow-Up Study of 69 Patients*

Abstract: TRH tests were performed in 206 clinically and biochemically euthyroid relatives of patients with Graves' disease. In 117 of the 206, T3 suppression tests were performed. Results revealed that 56 of the 206 (27.1%) showed abnormal responses to TRH. Twenty-nine of these (14.1%) revealed absent or decreased responses, and 27 (13.1%) revealed augmented responses to TRH. Eight of the 117 (6.8%) were T3 nonsuppressible. These eight subjects consisted of 4 subjects out of 17 hyperesponders and 4 subjects out of 90 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

1982
1982
2016
2016

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 58 publications
(23 citation statements)
references
References 12 publications
2
20
0
1
Order By: Relevance
“…It is known that relatives of Graves' patients may have immunologic abnormalities: about 25% may have positive LATS levels; some patients may have abnormal thyroid function tests, TRH stimulation tests, and/or T 3 suppression tests (283)(284)(285)(286)(287)(288)(289)(290). Wall et al in 1969 (284), reported the prevalence of TSH receptor antibodies in relatives of Graves' disease patients was 23%.…”
Section: Specificity Of Tsh Receptor Antibodies For Graves' Diseasementioning
confidence: 99%
“…It is known that relatives of Graves' patients may have immunologic abnormalities: about 25% may have positive LATS levels; some patients may have abnormal thyroid function tests, TRH stimulation tests, and/or T 3 suppression tests (283)(284)(285)(286)(287)(288)(289)(290). Wall et al in 1969 (284), reported the prevalence of TSH receptor antibodies in relatives of Graves' disease patients was 23%.…”
Section: Specificity Of Tsh Receptor Antibodies For Graves' Diseasementioning
confidence: 99%
“…TSH responsiveness was defined as being positive when the basal scrum TSH concentration was < 2.0 pU/ml and the peak value was > 6.2 pU/ml or if the basal value was > 2.0 pU/ml and ATSH (peak TSH-basal TSH) was > 5 pU/ml. Responses below those limits were considered to represent a hyporesponse, hyperresponsiveness to TRH was defined as a peak value of TSH > 35 pU/ml and a delayed response was defined as a peak value of TSH occurring later than 60 min after TRH injection [16,17]. …”
Section: Trh Testsmentioning
confidence: 99%
“…T3 suppression tests and TRH tests T3 suppression tests were performed by measuring the 24 h thyroid 131I uptake after administration of 75 µg T3 daily for 8 days. T3 suppressibility was defined as sup¬ pression of the 24 h thyroid 131I uptake after T3 admini¬ stration to more than 50% of the initial uptake before T3 administration (Tamai et al 1980). TRH tests were performed by injecting iv 500 µg synthetic TRH (Tanabe Seiyaku), and blood samples for TSH concentrations were obtained 0, 30, 60 and 90 min after TRH injection.…”
Section: Classification Ofthyroid Statusmentioning
confidence: 99%